Perlindungan Hukum Terhadap Perawat yang Bertugas Tanpa Pendampingan Dokter di Puskesmas Pembantu (Pustu) - Sukindar Sukindar (Prodi Ilmu Administrasi Negara, 2016)
The nurse is one of the important organs in health care centers, in addition to other health professionals such as doctors, midwives, nutritionists, health analyst, and others who are a team that can not be separated from one another in their duty to provide health care that is optimal to community.As the spearhead of duty in Community Health Centres, the main tasks of the nurse is to implement Nursing, which perform the nursing process from simple to complex, in collaboration with a team of other health professionals such as doctors, physiotherapists, nutritionists and other other critical identifying nursing services required include discussion or exchange of opinion in determining the form of services further, and not the health personnel assigned to provide treatment to patients like a doctor, as stipulated in the Decree of the Minister of Health of the Republic of Indonesia Number 1239 2001 On Registration and Practice Nurses.The phenomenon that occurs today is the discrepancy application of authority among health workers, both among doctors, midwives and nurses, that there are some actions that are kewenagan doctor but worked by nurses mainly stationed in health centers, as well as establish a diagnosis, prescribe medication , conduct treatment measures within and outside the health center building, inspection kehamilandan delivery assistance.This paper aims to determine the limits of authority as well as the nurse in charge of legal protection, especially for nurses on duty without the assistance of doctors in public health centers. By using normative juridical research method, the results of this paper is expected to provide knowledge about the importance of legal knowledge for nurses, so they are more cautious in the line of duty.